The Evolution of Multimodality Therapy for Malignant Pleural Mesothelioma - Zauderer, Marjorie G. (2011)
Malignant pleural mesothelioma (MPM) is a rare neoplasm of the pleural surfaces that has been associated with asbestos exposure. MPM generally spreads locally along the ipsilateral pleura, especially at presentation, with distant metastatic disease typically seen only in the later stages of the disease course. As such, surgical resection and other local therapies have long been pursued as a primary form of treatment. Surgical options include debulking of the pleura by pleurectomy/decortication (P/D), or a more aggressive extrapleural pneumonectomy (EPP) which also involves removal of the lung, diaphragm, and involved pericardium. Even after major resection, MPM almost always recurs locally and has a poor prognosis. As such, many groups have pursued multimodality therapy, treating resectable patients with extrapleural pneumonectomy (EPP), along with hemithoracic radiation to decrease the risk of local recurrence, and chemotherapy to decrease the risk of distant metastatic disease. However, EPP is associated with significant morbidity and mortality, and many patients are not candidates for EPP due to underlying comorbid medical conditions. Additionally, many patients are unable to tolerate complete courses of adjuvant therapy after EPP. A large, multi-center retrospective analysis comparing EPP to pleurectomy/decortication (P/D) demonstrated better outcomes among those who underwent P/D. One challenge associated with P/D has been the delivery or radiation to the removed pleura with an intact lung. Yet, advances in radiation technique have allowed the exploration of high-dose radiation therapy after P/D. The ideal timing of chemotherapy relative to surgery, and the role of intracavitary chemotherapy continue to be controversial issues. Clearly, MPM requires a multi-disciplinary approach and, due to the myriad of open questions, much effort continues to focus on identifying the optimal combination of surgery, chemotherapy, and radiation.